Implant survival and patient-reported outcome following total hip arthroplasty in patients 30 years or younger: a matched cohort study of 1, 008 patients in the Swedish Hip Arthroplasty Register. (4th May 2019) - Mohaddes, Maziar; NaucléR, Emma; Kärrholm, Johan; Malchau, Henrik; Odin, Daniel; Rolfson, Ola
Abstract : Background and purpose — The outcome of total hip arthroplasty (THA) in younger patients is suggested to be inferior compared with the general THA population. There is a lack of studies with long-term follow up for very young patients. We report on implant survival and patient-reported outcome in patients aged 30 years or younger. Patients and methods — Data on THAs performed in Sweden between the years 2000 and 2016 were included. There were 504 patients 30 years or younger with complete demographic and surgical data (study group). A matched comparison group older than 30 years was identified. Implant survival was analyzed using the Kaplan–Meier method. Patient-reported outcome was analyzed in a subgroup of patients. Results — The 10-year and 15-year implant survivorship for the study group was 90% and 78%, respectively. The corresponding figures for the patients older than 30 years were 94% and 89%. The median preoperative EQ-5D index was lower in the study group; the improvement in EQ-5D index was similar between the study and the comparison groups. The preoperative EQ-VAS was lower and the improvement in EQ-VAS at 1 year was larger in the study group. Interpretation — The promising 10-year implant survival and 1-year improvement in patient-reported outcome suggests that THA is a feasible option in the patients 30 years or younger.